STANDARDIZATION OF VARNYA DRAVYA (COMPLEXION PROMOTERS) WITH SPECIAL REFERENCE TO YASHTIMADHU AND MANJISHTA CHURNA – AN ANALYTICAL STUDY (AYUSHDHARA, 2020)
Standardization of drugs refers to the confirmation of its identity and determination of the quality and purity. Herbal drug technology is used for converting botanical materials into medicines, where standardization and quality control with proper integration of modern scientific techniques and traditional knowledge are important. However, the quality control and quality assurance still remains a challenge because of the high variability of chemical components involved. Most of the pharmaceutical industries are using substitute drugs in place of authentic drugs. So to manufacture and deliver the best quality drugs, it is essential to authenticate the raw drugs. Keeping the current inclination in mind, Varnyadravya or the complexion promoting drugs such as Yashtimadhu (Glycirrhizia glabra) and Manjishtha (Rubia Cordifolia) churna were subjected for standardization procedures. From the current study, genuinity indicating parameters for both Yashtimadhu churna (powder) and Manjishthachurna were derived.